Āsmānī naghme aw lāhūtī sarodūnah - Ḥabībī, ʻAbd al-Ḥayy, 1910- (Da Afghānistān da ʻUlūmo Akāḍemī, da Zhabo aw Adabiyāto ʻIlmī aw Taḥqīqī Markaz, Puṣhto Ṭolạnah, 1982)
Critical study of Pushto literature.